Формування результативної системи управління в контексті трансформаційних перетворень - Судомир, С. М. (НТУ "ХПІ", 2013)
Формування результативної системи управління в контексті трансформаційних перетворень

In this paper, principles system of management system generating of enterprises potential is systematized and updated, stages of organizational units’ progress are developed. To ensure effective use of advanced management structures the model of behaviors type correlation based on the criterion of activity, leadership styles, areas of resources disposal and accountability for using resources was proposed. The system changes of existing management structures depending on the farms size was developed
Keywords: результативність; ринок; процес; стадії розвитку; моніторинг; працівники; effectiveness; system; management; management; process; development stages